Detoxification of Deoxynivalenol by a Mixed Culture of Soil Bacteria With 3-epi-Deoxynivalenol as the Main Intermediate - Zhai, Yaoyao; Zhong, Lei; Gao, Hui; Lu, Zhaoxin; Bie, Xiaomei; Zhao, Haizhen; Zhang, Chong; Lu, Fengxia (Frontiers in Microbiology, 2019)
Deoxynivalenol (DON) is a widely distributed mycotoxin that frequently occurs in various agricultural raw materials and feeds. DON acts as a virulence factor that accelerates the spread of plant diseases; moreover, its accumulation in grains causes yield loss and serious health problems to humans and livestock. Biodegradation of DON into less- or non-toxic substances using naturally existing microorganisms is considered the best approach for DON detoxification. Although various single isolates and mixed cultures capable of detoxifying DON have been reported, details of the metabolic pathways and the degrading enzymes/coding genes involved are scarce. In this study, we aimed to isolate DON-degrading bacteria from soil samples and explore the mechanisms. Toward this end, 85 soil samples collected from different provinces in China were enriched under aerobic conditions with mineral media containing 50 μg/mL DON as the sole carbon source. The bacterial consortium LZ-N1 exhibited highly efficient and steady DON-transforming activity. High-throughput sequencing was used to characterize the composition of the involved microflora, and analysis of 16S rRNA sequences indicated that LZ-N1 was composed of at least 11 bacterial genera, with Pseudomonas accounting for nearly half the relative abundance. Co-incubation of a mixed culture of two novel strains from the LZ-N1 consortium, namely Pseudomonas sp. Y1 and Lysobacter sp. S1, showed sustained transformation of DON into the metabolite 3-epi-deoxynivalenol, with no degradation products detected after 72 h. The cell-free supernatant, lysate and cell debris of the mixed culture possessed DON-degrading ability, with the supernatant reaching a DON degradation rate of 100% within 48 h. This is the first report of two-step enzymatic epimerization of DON by a mixed culture, which may provide a new insight into this pathway for future applications in detoxification of DON-contaminated cereals and feed.